The impact of the External Auditor’s commitment to the ethics of the profession in reducing the manipulation of financial statements - Muhammad, Abd al-Wahhab Musa al-Jaali; Mohamed, Abdel Rahman Omar Ahmed (Journal of Economic, Administrative and Legal Sciences, 2017)
The aim of the research was to identify the impact of the external auditor’s commitment to the ethics of the profession in reducing the manipulation of the financial statements. To achieve this goal, the descriptive analytical approach was followed for its compatibility and the nature of the research. A total of 75 questionnaires were distributed to the members of the community. A total of 58 questionnaires were obtained with a recovery rate of 77.3%. For the purpose of analyzing the data and testing the hypotheses, the statistical packages were used for social studies. One of the findings of the research is that the external auditor’s adherence to the basic principles of professional ethics reduces the manipulation of the financial statements. The results of the statistical analysis have confirmed that the compatibility in the practice of auditing and scientific qualification of the auditor leads to adherence to the ethics of the profession. The study recommended conducting more future studies related to the ethics of the accounting and auditing profession, developing the performance of legal accountants regarding the ethics of the auditing profession, and the need to organize specialized workshops and conferences that deal with the ethics of the profession which contributes to enhancing the auditors’ compliance with professional ethics and professional rules of conduct.